Mengembangkan Kecerdasan Spiritual Anak di Sekolah Dasar (Paradigma Profetik) - Budi Putra Septian; Abdul Wachid B.S. (STKIP Andi Matappa Pangkep, 2021)
This paper was an research result of simple using the literature study of several references to support this notion of developing intelligence spiritual child in primary school with the approach. Profetik paradigm methods used in writing this deskritip-kualitatif, the collection of data using, observation interviews and dokumnetasi. The subject of study that public school students VI Negarayu 01. According to the results from research in intelligence was the core of spiritual awareness someone able to realize who she was and how he can give meaning of the intelligence spiritual children should be sharpened and trained as early as possible that they may be personally good. That is related to tips or manner by teachers in developing: spiritual intelligence in children are a good example (spiritual teacher), for students help children in formulating mission, his life read scripture together and clear, telling tales, spiritual leaders and the discussed several spiritualy, problem with perspective involving children in the religious rituals, read a poetry, or song, spiritual and inspiring bringing children to enjoy natural beauty, took him to the people who suffer from, follow enclose the. in social activities.